Ambiguities of Space and Control: When Refugee Camp and Nomadic Encampment Meet. (1st January 2014) - Wilson, Alice
Abstract : This article explores sedentarisation as a process of inherent tension between the rupture and preservation of values associated with mobility. This tension is compelling when mobile pastoralists settle in refugee camps. Refugee camps may resemble nomadic encampments in material infrastructure and (alleged) non-permanence. Yet refugee camps contrast with nomadic encampments in facilitating control and evoking, through its disruption, rootedness. In the case of refugees of mobile pastoralist heritage from the disputed territory of Western Sahara, the tension in the meeting of nomadic encampment and refugee camps sees the nomadic encampment reproduced and transformed in the refugee camp. This creates ambiguities of space and control.